2006
DOI: 10.1097/01.hjr.0000201515.59085.69
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on respiratory muscle oxygenation in children with congenital heart disease

Abstract: It is concluded that general physical training at submaximal intensity induces better aerobic fitness and improves respiratory muscle oxygenation in children with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 40 publications
(62 reference statements)
1
39
0
Order By: Relevance
“…McCall & Humphrey 30 Exercise capacity (treadmill exercise test) Improvement in exercise capacity Minamisawa et al 31 Exercise capacity (bicycle ergometer) 7% improvement in VO 2peak Opocher et al 34 Exercise capacity (treadmill exercise test) 19% improvement in VO 2peak Rhodes et al 28 Exercise capacity (bicycle ergometer) 22% improvement in VO 2peak Rhodes et al 28 Pulmonary function 7% improvement in FEV1 Moalla et al 27,29 Exercise capacity (bicycle ergometer) 8.1% improvement in VO 2peak Moalla et al 27 Six-minute walk 13% improvement in walking distance Moalla et al 29 Oxygenation respiratory muscles (NIRS) 28% improvement in respiratory muscle oxygenation Moalla et al 29 Pulmonary function Nonsignificant improvements in FEV1 (7.5%), FVC (6.2%), TLC (4.2) and MVV (5.7%) Brassard et al 23 Exercise capacity (bicycle ergometer test) No significant improvement in VO 2peak Brassard et al 23 Muscle strength No significant improvement in MVC Brassard et al 23 Blood pressure Significant improvement in ergoreflex culation. All six published studies showed that exercise training could improve exercise capacity in patients with a Fontan circulation.…”
Section: Study Outcome Measure Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…McCall & Humphrey 30 Exercise capacity (treadmill exercise test) Improvement in exercise capacity Minamisawa et al 31 Exercise capacity (bicycle ergometer) 7% improvement in VO 2peak Opocher et al 34 Exercise capacity (treadmill exercise test) 19% improvement in VO 2peak Rhodes et al 28 Exercise capacity (bicycle ergometer) 22% improvement in VO 2peak Rhodes et al 28 Pulmonary function 7% improvement in FEV1 Moalla et al 27,29 Exercise capacity (bicycle ergometer) 8.1% improvement in VO 2peak Moalla et al 27 Six-minute walk 13% improvement in walking distance Moalla et al 29 Oxygenation respiratory muscles (NIRS) 28% improvement in respiratory muscle oxygenation Moalla et al 29 Pulmonary function Nonsignificant improvements in FEV1 (7.5%), FVC (6.2%), TLC (4.2) and MVV (5.7%) Brassard et al 23 Exercise capacity (bicycle ergometer test) No significant improvement in VO 2peak Brassard et al 23 Muscle strength No significant improvement in MVC Brassard et al 23 Blood pressure Significant improvement in ergoreflex culation. All six published studies showed that exercise training could improve exercise capacity in patients with a Fontan circulation.…”
Section: Study Outcome Measure Resultsmentioning
confidence: 99%
“…Two of the studies included children with congenital heart diseases other than Fontan circulation. [27][28][29] The characteristics of the six studies are displayed in table 1.…”
Section: Experimental Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…On completion of a variety of training programs, peak Vȯ 2 has been reported to increase 7% to 21% over baseline values. [586][587][588][589] Most of the improvement appears to be attributable to an increase in the oxygen pulse at peak exercise. 589 In one study, the short-term improvements were sustained 6 to 9 months after the termination of the rehabilitation program (1 year after the prerehabilitation study) and were associated with improvements in lifestyle, perceived exercise function, self-esteem, and emotional state.…”
Section: Exercise Training In Padmentioning
confidence: 99%
“…Many cardiopulmonary variables may contribute to a reduced exercise tolerance, including systolic and diastolic ventricular dysfunction, sinus node dysfunction, and changes in cardiac autonomic nervous activity, whereas reduced physical activity in these patients may further lead to reduced exercise tolerance. 4 Physical training at recommended levels may increase exercise tolerance, 5,6 while the use of different cardiopulmonary parameters in the evaluation of exercise tests may give more insight into the mechanisms of reduced exercise tolerance. These parameters include simple measures as peak work rate (WR peak ) and heart rate (HR) response to exercise, peak oxygen uptake (VO 2peak ), and more recently proposed measures as the ventilation to carbon dioxide exhalation (VE/VCO 2 ) slope.…”
Section: Introductionmentioning
confidence: 99%